Hyaluronic Acid And Its Role In Periodontal Healing: Asam Hialuronat dan Peranannya Dalam Penyembuhan Periodontal - Wulandari, Pitu; Amalia, Martina; Budi; Simanjuntak, Rio; Satria, Denny (TALENTA, 2022)
Hyaluronic acid is known as hyaluronan or hyaluronate, which has the function of increasing the mediator of periodontal regeneration. Hyaluronate acid has many roles in the early stages of inflammation, such as providing a structural framework through the interaction of hyaluronate with fibrin clots that modulate host inflammation and infiltration of the extracellular matrix of cells at the wound site so that this material becomes a therapeutic material used in various fields, especially in the field of periodontics. All periodontal tissues have shown the presence of hyaluronate, which is specifically concentrated in non-mineral tissues such as gingiva and periodontal ligament, which affects the growth, development, and repair of tissues in periodontal disease. The role of hyaluronic acid in periodontal healing will be discussed in this article.